The Role of Cholesterol during the Ovarian Maturation and Lipid Metabolism of Female Chinese Mitten Crab (Eriocheir sinensis) - Huixing Guo; Haokun Hua; Jianfeng Wang; Wei Qiang; Xiaoe Xiang; Wenbin Liu; Guangzhen Jiang (Aquaculture Nutrition)
In previous study, we found that the cholesterol requirement of Eriocheir sinensis was 0.27%, to further investigate the effects of cholesterol on health status, ovarian maturation, and lipid metabolism of female Eriocheir sinensis broodstock. Two diets containing 0% and 0.25% (actually 0.05% and 0.27%) cholesterol were fed to the female crabs (average weight: 49.21 ± 0.11 g) for 4 months and sampled once a month. The results showed that the body weight (BW), survival rate (SR), meat yield (MY), condition factor (CF), hepatosomatic index (HSI), and gonadosomatic index (GSI) of Eriocheir sinensis were significantly affected by treatment time and compared with the cholesterol deficient group, supplementing cholesterol significantly increased BW, HSI, and GSI (P<0.05). In addition, long-term lack of cholesterol will lead to a significant decrease in the activity of ACP, AKP, and SOD and a significant increase in the content of MDA. The histological results showed that cholesterol significantly increased the volume of oocytes (P<0.05). Further studies found that 0.27% cholesterol significantly increased the transcription levels of vtg and vgr in hepatopancreas and ovaries, which may be the main reason for the increase of oocyte size (P<0.05). When fed with 0.27% cholesterol diet, the contents of nutrients in hepatopancreas and ovaries increased significantly, especially lipids and cholesterol (P<0.05). Through the analysis of mRNA expression level of genes related to lipid metabolism, it was found that cholesterol enhanced the transcription level of genes related to lipid synthesis and transport in hepatopancreas, thereby promoting the accumulation of lipid in the organism. Furthermore, compared with control group, the levels of juvenile hormone (JH), 17β-estradiol (E2), methyl farnesoate (MF), and ecdysone in the organism were significantly increased after feeding a diet with 0.27% cholesterol (P<0.05). In summary, supplementing an appropriate amount of cholesterol in the diet can improve the growth performance of Eriocheir sinensis broodstock, enhance the body’s antioxidant and immune system, and promote the accumulation of nutrients in the ovaries, thereby promoting ovarian maturation.